Normal and Reversed-Phase HPTLC Methods for Simultaneous Estimation of Telmisartan and Metoprolol Succinate in Pharmaceutical Formulation. (5th December 2011) - Nawale, Prajakta S.; Shirkhedkar, Atul A.; Surana, Sanjay J.; Patil, Amod S.
Abstract : Two simple precise normal-phase (Method I) and reversed-phase (Method II) HPTLC/densitometry method have been developed for simultaneous determination of telmisartan and metoprolol succinate in bulk and in combined tablet formulation. Method I was developed with aluminium plates precoated with silica gel 60F254 S, and toluene : propanol : methanol : triethylamine (8 : 1 : 1 : 0.5 v/v) was used as as mobile phase. Method II was carried out using aluminium coated with RP-18 silica gel 60 F254 S HPTLC plates using methanol : water : triethylamine (6 : 4 : 0.5 v/v) as mobile phase. Both analyses were scanned with a densitometer at 242 nm. In Method I, good separation and resolution of drugs were achieved with R f values 0.45 ± 0.02 (telmisartan) and 0.70 ± 0.02 (metoprolol), while in Method II, telmisartan and metoprolol showed R f values 0.55 ± 0.02 and 0.41 ± 0.02, respectively. These methods can be used in routine pharmaceutical analysis.